PENGARUH MODEL PEMBELAJARAN MIND MAPPING DENGAN MEDIA PETA TERHADAP HASIL BELAJAR TEMATIK INTEGRATIF - Rizka Oktavianto; Anita Trisiana (JURNAL SINEKTIK, 2020)
This study aims to find out the influence of mind mapping learning model with map media on integrative thematic learning outcomes in grade 4 students at SDN 03 Bangsri Karangpandan SubDistrict 2018/2019. The sample and population of the study were all 29 students in grade IV. This type of research uses quantitative types. Data collection techniques using tests, observations, documentation and interviews. Analytical techniques and hypothesis testing using paired sample t-test. Based on paired sample t-test results obtained -thitung every aspect of learning results compared to -typhible with d.b (N-1) so (29-1)= 28 significant level of 5% which is -2,048. Results of cognitive aspects -thitung < -ttabel or - 42,585 <-2,048 so ha received, affective aspect results -6,782 <-2,048 so ha received, and results of psychomotor aspects-13,229 < -2,048 so that Ha was accepted and Ho rejected. In conclusion, there is an influence of Mind Mapping Learning Model With Map Media on Integrative Thematic Learning Results Proven To Be True, and acceptable.